Factors associated with frenotomy after a multidisciplinary assessment of infants with breastfeeding difficulties. (November 2020) - Diercks, Gillian R.; Hersh, Cheryl J.; Baars, Rebecca; Sally, Sarah; Caloway, Christen; Hartnick, Christopher J.
Abstract: Objective: Frenotomy for ankyloglossia has increased nearly 10-fold over the past few decades despite insufficient evidence that the procedure improves breastfeeding outcomes. There is no universally accepted method for identifying patients who may benefit from the procedure. The objective of this study is to determine if comprehensive feeding evaluations and targeted interventions can identify children who should undergo procedures, and to identify factors associated with lip or tongue frenotomy to treat breastfeeding difficulties. Methods: This observational quality improvement study followed infant-mother dyads between March 2018 and December 2019 referred to our tertiary care center for breastfeeding difficulties. Speech and language pathologists performed comprehensive feeding evaluations on infants prior to surgical consultation for frenotomy. Infants' oral anatomy and function and their ability to breast and bottle feed were assessed, and techniques for mothers to address feeding difficulties without a procedure were offered prior to surgical consultation. Infants either found success over a short observation period or underwent procedures (lip and/or tongue frenotomy). Results: 153 patients (mean age 47.0 days (stdev 39.0 days, 56.2% male) were referred for surgical division of the lingual frenulum. Following development of a program utilizing pediatric speech language pathologists to perform feeding evaluations prior to surgical consultation, 69.9% of patients subsequently did not undergo surgical procedures. 11 (23.9%) underwent labial frenotomy alone and 30 (65.2%) underwent both labial and lingual frenotomies. Frenotomy was associated with significantly increased worry subscale of the Feeding Swallow Impact Survey (FSIS) and decreased mean Breastfeeding Self Efficacy Scale score (p = 0.0001, p = 0.006, respectively). Tongue appearance was significantly associated with having a procedure, while lip appearance was not. The Bristol Breastfeeding Assessment Tool (BBAT) was lower in children undergoing tongue and/or lip frenotomy (p = 0.0006), while the Hazelbaker Assessment Tool for Lingual Frenulum Function (HATLFF) appearance and function scores were lower in children undergoing lingual frenotomy with or without lip frenotomy (p = 0.0008, p = 0.0009, respectively). Conclusions: The majority of patients referred for ankyloglossia may benefit from nonsurgical intervention strategies based on findings from comprehensive feeding evaluation. Frenotomy is associated with higher maternal feeding-related worry and reduced breastfeeding self-efficacy scores. While tongue appearance is associated with frenotomy, functional assessment is critical for identifying patients who may also benefit from lip frenotomy.